EP--BP Paraphrastic Alignments of Verbal Constructions Involving the Clitic Pronoun lhe (Linguamática, 2019)
This paper presents the alignment of verbal predicate constructions with the clitic pronoun lhe in the European (EP) and Brazilian (BP) varieties of Portuguese, such as in the sentences Já lhe arrumaram a bagagem --- Sua bagagem está seguramente guardada "His baggage is safely stowed away", where the EP dative proclisis lhe contrasts with the BP possessive pronoun sua. We have selected several different paraphrastic contrasts, such as proclisis and enclisis, clitic pronouns co-occurring with relative pronouns and negation-type adverbs, among other constructions to illustrate the linguistic phenomenon. Some differences correspond to real contrasts between the two Portuguese varieties, while others purely represent stylistic choices. The contrasting variants were manually aligned in order to constitute a gold standard dataset, and a typology has been established to be further enlarged and made publicly available. The paraphrastic alignments were performed in the e-PACT corpus using the CLUE-Aligner tool. The research work was developed in the framework of the eSPERTo project.
Keywords: Paraphrases, automated paraphrasing, verbal compounds, clitic pronouns, European Portuguese, Brazilian Portuguese, paraphrastic alignments